Pengaruh Penggunaan Aplikasi Flashcard Terhadap Hasil Belajar Mufrodat Bahasa arab - Ma'wa, Nurul; Indriana, Dina; Ubaidillah, Ubaidillah (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2024)
The purpose of the experimental study on the use of technology-based flashcard media is to improve vocabulary and understanding of Arabic vocabulary in grade VIII students at Daarul Ahsan Islamic Boarding School, Jayanti Tangerang. Researchers use quantitative methods with quasi-experimental theory with data collection methods used by researchers are interviews, observations and tests. The use of flashcard media has an influence on the learning outcomes of grade VIII students. This can be seen in the pre-test and post-test results with paired sample t test which shows a value (Sig 2 tailed) 0.000 less than 0.05. Then there is also a difference in value between the experimental class and the control class of the independent sample t test with a value of (Sig 2 tailed) 0.000 less than 0.05.